ANALISIS STRATEGI GURU DALAM MENGATASI KESULITAN FOKUS BELAJAR SISWA TUNARUNGU DENGAN ADHD DI PKBM IKHLAS BERSAMA - Nazwa Aulia Syahrani; Anisa Zahara; Sindy Rahmadani Sitorus; Utami Dwika Sari; Ramadhani (STKIP Subang, 2026)
This study aims to analyze teacher strategies for addressing learning difficulties for deaf students who also have Attention Deficit Hyperactivity Disorder (ADHD) at the Ikhlas Bersama Community Learning Center (PKBM). This study used a descriptive qualitative method with a case study approach. Data were obtained through participant observation, in-depth interviews with teachers and parents, and documentation of learning activities. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that teachers implemented several mutually reinforcing strategies to address students' learning difficulties, including the use of visual media, a classroom environment with minimal distractions, simple and gradual instruction, and a personalized approach through positive reinforcement and collaboration with parents. The integration of these four strategies helped students reduce cognitive overload, increase cognitive engagement, and maintain learning focu, longer through visual support, environmental structure, clear instructions, and consistent personal relationships.